Cultural Heritage Interpretation of Old Home and Historic House in the Old Town of Nakhon Lampang - Yodsurang, Patiphol; Wiyati, Werapong (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Old home and historic house cultural heritage remain in a large number in the Lampang Old Town. The area representing transformation and development of the past is one of the most popular tourist destinations. A total of 32 sites were identified as a special distinctive cultural property, where were selected as samples in this study. Besides, more than 900 distinctive buildings are influencing the historic urban landscape of Lampang Old Town. Most of them are being modified, adapted, utilized, and enriched with traditional elements in response to tourism economies and contemporary activities based on local-available resources. The two parts of survey was undertaken in research method conducting urban-level rapid survey and site-specific survey based on cultural tourism, cultural heritage, historical urban landscape. sense of place and interpretation of cultural heritage. The result reveals 3 groups of the old home and historic house cultural heritage presenting interpretation patterns as; 1) no interpretation tools, but create sense of urban landscape consisting of residential houses, 2) no interpretation tools, but create sense of the buildings itself and urban landscape consisting of shops, restaurants, accommodation, and offices that are not open to the public, and 3) interpretation tools available, and create sense of the buildings itself and urban landscape consisting of museums and knowledge center that are open to the public. Among those old houses and historic houses, shops, restaurants, accommodation, and offices are found that the visitors can use, access, and interact with various parts of the building over a longer period, without restriction, than in other groups. Thus, this was able to create a sense of place and immense them to the architectural atmosphere of the place. As a result, adaptive reuse of the building to accommodate contemporary tourism and economic activities, it is necessary to consider the availability in utilization of building elements, place, and space that will enhance a better visitor perception in architecture.